Access to Disentangled Ultrahigh Molecular Weight Polyethylene via a Binuclear Synergic Effect. (14th December 2022) - Zhang, Zhen; Kang, Xiaohui; Jiang, Yang; Cai, Zhongyi; Li, Shihui; Cui, Dongmei
Abstract: Disentangled ultrahigh molecular weight polyethylene ( dis ‐UHMWPE) has excellent processability but can be achieved under extreme conditions. Herein, we report ethylene polymerization with the binuclear half‐sandwich scandium complexes C1‐Sc2 and C2‐Sc2 to afford UHMWPE. C1‐Sc2 bearing a short linker shows higher activity and gives higher molecular weight PEs than C2‐Sc2 containing a flexible spacer and the mononuclear Sc1 . Strikingly, all UHMWPEs isolated from C1‐Sc2 under broad temperature range (25–120 °C) and wide ethylene pressures (2–13 bar) feature very low degree of entanglement as proved by rheological test, DSC annealing study and SEM. These dis ‐UHMWPEs are facilely mediated solid‐state‐process at 130 °C and their tensile strength and modulus reach up to 149.2 MPa and 1.5 GPa, respectively. DFT simulations reveal that the formation of dis ‐UHMWPE is attributed to the binuclear synergic effect and the agostic interaction between the active center and the growing chain. Abstract : A convenient synthetic method is reported to tie together two half‐sandwich scandium dialkyls with short linkers. The binuclear complex C1‐Sc2 exhibits extremely high activity for ethylene polymerization and affords ultrahigh molecular weight polyethylene (UHMWPE) featuring low entanglement degree and excellent processing capability under a wide range of reaction temperatures (25–120 °C) and ethylene pressures (2–13 bar).